Ultrahigh-speed absolute temperature sensing using ferroelectric HfO2 enabled by transient negative differential capacitance - Kumar, Mohit; Park, Hayoung; Seo, Hyungtak (Nanoscale, 2024)
Conventional ferroelectric polarization-driven temperature sensors, like pyroelectric sensors, often face challenges such as slow response times, limited compatibility with conventional nanoelectronics, and inability to operate under constant temperature conditions. These shortcomings hinder their adaptability to a broad range of applications, especially when compared to thermal and optical sensors. To address these challenges, we introduce a proof-of-concept methodology that enables ferroelectric-based pyroelectric sensors to measure absolute temperatures with high accuracy and speed. Specifically, we demonstrate that a perturbation pulse (+0.8 V, duration = 180 ns) can serve as an effective probe for quantifying both absolute and dynamic temperatures across ferroelectric hafnium zirconium oxide (HZO) nanolaminates. The device demonstrates an ultrafast response time of ∼50 nanoseconds, offering one million readings per second and a temperature sensing accuracy comparable to the state-of-the-art temperature sensing accuracy of 1.0 K. The observed performance is attributed to the temperature-dependent change of transient negative differential capacitance and effective ferroelectric polarization of HZO. For potential applications, we successfully integrated the sensor with a commercially available universal serial bus interface, thereby demonstrating real-time temperature monitoring during data transfer and environmental heating activities. Our research significantly broadens the range of applications for pyroelectric sensors for both steady-state and rapid dynamic temperature measurements.
Keywords: Constant temperature; Differential capacitance; Ferroelectric polarization; HfO 2; Pyroelectric sensors; Sensing accuracy; Temperature sensing; Time limited; Ultra high speed; Zirconia oxide